Preparation of porous carbon anode materials for lithium-ion battery from rice husk - Yu, Kaifeng; Wang, Yu; Wang, Xiaofeng; Liu, Weiping; Liang, Jicai; Liang, Ce (Materials letters, 2019)
Porous carbon materials have been prepared by using natural SiO2 in rice husk as the template. When used as anode for lithium ion battery, it displayed an excellent electrochemistry performance of high specific capacity and super coulomb efficiency. [Display omitted] •Porous carbon material is prepared using natural SiO2 in rice husk as a template.•This carbon material has exhibited excellent specific capacity after 500 cycles.•The coulomb efficiency of porous carbon anode is close to 100%. Porous carbon anode materials is synthesized by using rice hull natural SiO2 as templates, and the materials with a specific surface area of 332 m2g−1 has possessed micropores, mesopores and macropores microstructure. The materials display a high capacity of 756.9 mAhg−1 after 150 charge-discharge cycles at 0.2C and 620 mAh/g after 600 cycles at 2C, the coulomb efficiency is close to 100%. The excellent performance makes it a promising candidate for high-capacity lithium-ion batteries.